Study on the Management of the Wanggu River Basin in Southeast Sulawesi: Literature Review - La Ode Muhammad Erif; La Baco Sudia; Surya Cipta Ramadhan Kete; Asramid Yasin; Muhammad Saleh Qadri (International Journal of Technology and Education Research, 2025)
The concept of Integrated Watershed Management essentially involves participatory management by multiple stakeholders, focusing on conservation and sustainable use through an ecological approach that emphasizes the interdependence between humans and nature. The Wanggu Watershed, located in Southeast Sulawesi, is characterized by high dynamics due to various human activities such as agriculture, plantations, forestry, and residential development, all of which influence its performance and carrying capacity. The extent of critical and moderately critical land in the Wanggu Watershed still qualifies it as an area with a high need for critical land rehabilitation. The percentage of vegetation cover, particularly forest cover, remains low and is in poor condition. This study aims to evaluate the watershed management practices implemented in the Wanggu Watershed. The water bodies included in the study comprise lakes, rivers, estuaries, seas, bays, and straits. The results indicate that the condition of vegetation cover—especially forest cover—is still poor, and the erosion index is high. Several soil parameters further reveal that the current watershed management in Wanggu is associated with low land carrying capacity. Therefore, improved land management and conservation efforts are necessary to enhance the watershed's performance and sustainability.